Lifestyle characteristics in adolescent female football players: data from the Karolinska football Injury Cohort - Fältström, A.; Skillgate, E.; Weiss, N.; Källberg, H.; Lyberg, V.; Waldén, M.; Hägglund, M.; Asker, M.; Tranaeus, U. (BMC Sports Science, Medicine and Rehabilitation, 2022)
Background Normative values of lifestyle characteristics in adolescent female football players may be used by clinicians and coaches to take actions because the potential important for well-being, performance on the pitch, and risk of injury. The aim was to report descriptive characteristics of lifestyle factors in adolescent female football players and potential changes over 1 year.